AMBIGUITY IN SONG LYRICS OF THE BEST DAY BY TAYLOR SWIFT - Pratiwi, Imas Meilisa Dewiworo (MEMACE: Jurnal Linguistik, Pendidikan Bahasa Indonesia, dan Asing, 2023)
The purpose of this study is to identify ambiguity in the lyrics of the song entitled "The Best Day" created and sung by Taylor Swift. This research uses descriptive methods to analyze the data. The research data was collected from the lyrics of the song "The Best Day". The result of this research shows that: There are eight ambiguities, four structural ambiguities and four lexical ambiguities in the lyrics of the song "The Best Day". Taylor Swift uses more than a few ambiguities to tell her real life as a child through her song lyrics, such as: homonymy, homophones, homographs, full homonymy, partial homonymy, polysemy, morphology, and syntax. She shares that when she was five years old, she could already feel everything that happened in her life, and she believed that her mother was not afraid of anything that harmed her, her mother would always take care of her. She also felt that her father was the greatest father in the world, always taught her how to be a strong child. Swift was also always proud of her little brother; she taught that he was better than her. This study is important to know the message or meaning that the singer or song writer wants to convey in his/her work.